Teachers’ personal competencies in fostering student character through Pancasila education - Siti Rohana; Sugeng Kurniawan; Mabruri Mabruri (Universitas Ahmad Dahlan, 2026)
Teachers’ personality competencies play a crucial role in shaping students’ character through Pancasila Education instruction. However, research explaining how these competencies are implemented in the classroom and the mechanisms by which they shape students’ character in the context of integrated Islamic elementary schools remains limited. This study aims to explore the role of teachers’ personal competencies in building students’ character through Pancasila Education instruction at SDIT Al-Akhyar Muara Bungo. The study employs a qualitative descriptive approach, involving the school principal, Pancasila Education teachers, and students selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the interactive model developed by Miles, Huberman, and Saldaña and validated through triangulation of sources and techniques. The results identified six dimensions of teachers’ personality competencies: exemplary behavior, discipline, responsibility, wisdom and prudence, compassion, and social interaction. These six dimensions are consistently implemented through role modeling, habit formation, and positive interactions, thereby supporting the development of students’ discipline, responsibility, social awareness, and social interactions. This study offers a conceptual model that explains the relationship between teachers’ personality competencies, the implementation of Pancasila education, the process of value internalization, and the character development of students. These findings contribute to the development of character education and the strengthening of teachers’ personality competencies in elementary schools.